READINESS OF PROSPECTIVE TNI OR POLRI ACADEMY CADETS TO FACING PSYCHOLOGICAL TEST PREPARATION - Billy Martasandy (Adisam Publisher, 2024)
Objective study This is to determine the readiness of prospective TNI and POLRI academy cadets to face psychological test preparation. The method used is qualitative, with a study field. As for participants in the study, these are two prospective TNI and POLRI cadets. Results study This means that an individual's readiness to face psychological tests is influenced by various factors. Some of these factors include previous experience, learning approach, social support, mental and emotional readiness, understanding of psychological tests, motivation, commitment, awareness of the importance of psychological tests, self-reflection, and personal readiness. In the context of prospective TNI cadets, it was found that their readiness to face psychological tests varied, with some individuals feeling ready and confident after intensive preparation and practice, while others may feel less prepared or anxious about facing the test.